Characterisation of proteins and RNA expressed in syncytiotrophoblast membrane extracellular vesicles (STB-EVS) in preeclampsia - Awoyemi, T (2022)
Introduction: Preeclampsia is a complication of pregnancy that affects 2-8 % of women worldwide. It is one of the leading causes of maternal deaths and premature birth. It is diagnosed by elevated blood pressure (≥ 140/90 mmHg), proteinuria, and/or end-organ damage. Although the precise mechanisms are not fully elucidated, the placenta is involved in this disease process. However, one theory is the role of extracellular vesicles STB-EVs, which are membrane-bound biomolecules that range between 30-1000 nm in size released by the placenta and detected in the circulation. STB-EVs have been reported to be higher in the circulation in PE compared to Normal pregnancy. In addition, the phenotype of the STB-EVs is believed to be different in PE compared to NP. However, it is unclear if the clinical manifestations attributable to STB-EVs in PE are a) because PE STB-EVs are more abundant in circulation, b) because they are of a different phenotype (bigger with a different cargo), or c) a combination of both. This thesis builds on the second premise.